2004
DOI: 10.5005/jcdp-5-2-27
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur By-Product: The Relationship between Volatile Sulphur Compounds and Dental Plaque-Induced Gingivitis

Abstract: The purpose of this study was to evaluate the relationship between volatile sulphur compounds (VSC) and gingival health status, and to monitor the changes in VSC in early dental plaque-induced gingivitis. Using an experimental gingivitis model, twelve subjects between 19 and 28 years old, with a healthy gingival status, refrained from brushing and flossing one randomly selected half of the mandibular arch for two weeks. At baseline and during six subsequent appointments, gingival inflammation (GI), bleeding on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The analysis indicated that the exhaled VSCs concentrations in periodontitis patients were greater and correlated with the presence of Bacteroides forsythus , P. gingivalis and Prevotella intermedia (Awano et al., ). Similarly, increased production of VSCs contributing to the presence or exacerbation of halitosis has been widely described in oral cavity diseases (van den Broek et al., ), including but not limited to gingivitis (Zhou, McCombs, Darby, & Marinak, ), periodontitis (Tsai et al., ), xerostomia (Bollen & Beikler, ), mucosal ulcerations, and deep dental lesions (van den Broek et al., ; Cortelli, Barbosa, & Westphal, ). These findings strongly suggest that identifying exhaled VSCs and monitoring their levels could serve as a simple non‐invasive diagnostic tool for oral halitosis.…”
Section: Volatile Sulfuric Compounds: From Bad Smell To Potential Biomentioning
confidence: 93%
“…The analysis indicated that the exhaled VSCs concentrations in periodontitis patients were greater and correlated with the presence of Bacteroides forsythus , P. gingivalis and Prevotella intermedia (Awano et al., ). Similarly, increased production of VSCs contributing to the presence or exacerbation of halitosis has been widely described in oral cavity diseases (van den Broek et al., ), including but not limited to gingivitis (Zhou, McCombs, Darby, & Marinak, ), periodontitis (Tsai et al., ), xerostomia (Bollen & Beikler, ), mucosal ulcerations, and deep dental lesions (van den Broek et al., ; Cortelli, Barbosa, & Westphal, ). These findings strongly suggest that identifying exhaled VSCs and monitoring their levels could serve as a simple non‐invasive diagnostic tool for oral halitosis.…”
Section: Volatile Sulfuric Compounds: From Bad Smell To Potential Biomentioning
confidence: 93%
“…Sulfide levels were measured using the Diamond Probe/Perio 2000 system (Diamond General Development Corp., USA). The system is a dental device designed to detect sulfide concentrations of various forms (S, HS, H 2 S, and CH 3 SH) within the gingival sulcus [ 21 ] and combines a conventional Michigan “O” style dental probe with a sulfide sensor. Radiographs were obtained to determine any radiographic bone loss.…”
Section: Methodsmentioning
confidence: 99%
“…When gram-negative bacteria invade the underlying connective tissue of the periodontium, an inflammatory reaction can begin and result in a tissue disruption [ 72 ]. Several clinical studies have reported that sulfide by-products are associated with periodontal diseases, especially including plaque-induced gingivitis [ 72 , 73 , 74 , 75 , 76 , 77 ]. Many sulfide detection tools have also been introduced, e.g., Halimeter ® (Interscan Corp., Simi Valley, CA, USA), Oral Chroma™ (Nissha FIS, Osaka, Japan), and Breathtron ® (Yoshida, Tokyo, Japan), but they are designed for halitosis sensing and unavailable for diagnosing of PDs in the gingiva sulcus and periodontal pockets.…”
Section: Diagnosis With the Available Chairside Probing Toolsmentioning
confidence: 99%